A review on CYP11A1, CYP17A1, and CYP19A1 polymorphism studies: candidate susceptibility genes for polycystic ovary syndrome (PCOS) and infertility - Heidarzadehpilehrood, Roozbeh; Pirhoushiaran, Maryam; Abdollahzadeh, Rasoul; Osman, Malina; Maryam Sakinah; Nordin, Norshariza; Abdul Hamid, Habibah (MDPI, 2022)
Polycystic ovary syndrome is a multifactorial condition associated with reproductive and endocrine organs and might cause infertility and metabolic abnormalities in childbearing age. PCOS seems to be a multifactorial disorder resulting from the combination of several genetic and environmental factors. Little research has been conducted to date on the impact of polymorphisms in infertility. We aim to review the appearance of polymorphisms in females of diverse ethnicities and their effect on infertility in the population with polycystic ovary syndrome. There have been numerous reports of the importance of the steroidogenesis pathway and genetic variants in PCOS pathogenesis. The most important genes that play a role in the aetiology of PCOS are CYP11A1, CYP17A1, and CYP19A1. We evaluated the occurrence of polymorphisms in various ethnicities in the CYP11A1, CYP17A1, and CYP19A1 genes and their efficacy on increasing PCOS risk with infertility. Our findings revealed that polymorphisms in various ethnicities are associated with the risk of PCOS with infertility. Although conflicting results regarding CYP11A1, CYP17A1, and CYP19A1 polymorphisms and their influence on PCOS with infertility have been reported in a small number of papers, the authors feel this may be attributable to the sample size and ethnic composition of the examined populations. In conclusion, our study strongly suggests that the CYP11A1, CYP17A1, and CYP19A1 genes might significantly enhance the probability of developing PCOS with infertility.